Endogenous growth and changing sectoral composition in advanced economies - Luigi Bonatti; Giulia Felice (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2004)
Despite the striking evidence of the changing sectoral composition in employment and output shares characterizing the growth process, structural change is usually disregarded in growth modeling. In contrast, we focus on how structural change can affect aggregate growth by presenting a two-sector model with a progressive industry (manufacturing), which exhibits endogenous technological progress and produce both for consumption and for investment, and a technologically stagnant industry (services), which produces only for consumption. Within this framework, we show under what conditions on preferences perpetual growth can be generated. In particular, the paper demonstrates that positive long-term growth is possible even if what households spend on services tends to increase more than proportionally than their total consumption expenditure, namely when preferences are non-homothetic. This is at odds with previous literature arguing that Baumol's asymptotic stagnancy applies when the stagnant industries supply final products. Moreover, the paper does not limit its attention to the balanced growth path: numerical examples illustrate how the transition path displays the regularities which appear to characterize the structural dynamics in advanced economies.
Keywords: O41; 330; balanced growth; structural change; non-homothetic preferences; Neue Wachstumstheorie; Strukturwandel; Präferenztheorie